2016
DOI: 10.1016/j.molcel.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation of MDH1 by CARM1 Inhibits Glutamine Metabolism and Suppresses Pancreatic Cancer

Abstract: Distinctive from their normal counterparts, cancer cells exhibit unique metabolic dependencies on glutamine to fuel anabolic processes. Specifically, pancreatic ductal adenocarcinoma (PDAC) cells rely on an unconventional metabolic pathway catalyzed by aspartate aminotransferase, malate dehydrogenase 1 (MDH1), and malic enzyme 1 to rewire glutamine metabolism and support nicotinamide adenine dinucleotide phosphate (NADPH) production. Here, we report that methylation on arginine 248 (R248) negatively regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 51 publications
1
119
0
Order By: Relevance
“…Glutamine is a critical metabolite that participates in energy metabolism, redox homeostasis, nucleotide, and amino acid biosynthesis 22. Moreover, as a major tricarboxylic acid (TCA) cycle carbon source in cancerous cells, glutamine is necessary to support cancerous cells growth and proliferation 23. The frequently activate glutamine consumption in cancerous cells was further proved by our MSI assay.…”
Section: Functional Metabolites Based Molecular Histologymentioning
confidence: 70%
“…Glutamine is a critical metabolite that participates in energy metabolism, redox homeostasis, nucleotide, and amino acid biosynthesis 22. Moreover, as a major tricarboxylic acid (TCA) cycle carbon source in cancerous cells, glutamine is necessary to support cancerous cells growth and proliferation 23. The frequently activate glutamine consumption in cancerous cells was further proved by our MSI assay.…”
Section: Functional Metabolites Based Molecular Histologymentioning
confidence: 70%
“…However, TCGA database revealed MDH1 amplification in solid tumor models (Figure 4) suggesting that, unlike in cell culture models, the availability of substrate drives selection for MDH1 over-expression. A recent study also revealed MDH1 amplification and increased MDH1 activity in human PDAC samples(30). In demonstrating the importance of MDH1-mediated malate synthesis to cytosolic NAD regeneration in highly glycolytic cells, this study offers fresh insights into metabolic alterations aimed at meeting the demands of growth and division and highlights the need for alternative strategies to target the increased consumption and utilization of glucose in cancers.…”
Section: Discussionmentioning
confidence: 85%
“…The efficiency arises from the fact that malate can be further metabolized for biomass, energy generation or ROS control, whereas lactate is primarily secreted into the extracellular environment as waste. A recent study has also demonstrated the importance of MDH1 activity in KRAS driven pancreatic ductal carcinomas to control ROS by providing malate as a substrate for malic enzyme and NADPH production(30). Moreover, LDHA inhibition did not significantly repress growth in Jurkat cells unless MDH1 was knocked out.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of ACSL1, carbonic anhydrase, and SCD1 in cancer are all supported by literature. Although MDH1 inactivation inhibits pancreatic cancer growth by suppressing glutamine metabolism 41 , the role of MDH1 in de novo fatty acid synthesis has not been previously studied, and may be a potential new target to manipulate fatty acid metabolism for prostate cancer treatment.…”
Section: Resultsmentioning
confidence: 99%